#TITLE_ALTERNATIVE# - RAMDIANI SETIADJI (NIM 10107041); Pembimbing : Dr. Nuning Nuraini, ARINI
This final project will discuss mathematic models to describe the in vivo dynamics of HTLV-I (Human T-lymphotropic Virus Type I) infection for the slow rate of evolution of HTLV-I. There are two models, first is the basic model of virus replication in T cells (infection transmission models) and the second is mitotic transmission models. Both models would be analyzed equilibrium points and the basic reproduction number (Ro) to determine the persistence of the virus in the body. There is the bistability phenomenon of two equilibrium points in the first model. Moreover, both transmission process would be analyzed and the explanation for the low rate evolution of HTLV-I in the body